2002
DOI: 10.1038/sj.npp.1300086
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Effects on Prepulse Inhibition Across-Species: Replication and Parametric Extension

Abstract: Despite the similarities of prepulse inhibition (PPI) of the startle reflex and its apparent neural regulation in rodents and humans, it has been difficult to demonstrate cross-species homology in the sensitivity of PPI to pharmacologic challenges. PPI is disrupted in rats by the indirect dopamine (DA) agonist amphetamine, and while studies in humans have suggested similar effects of amphetamine, these effects have been limited to populations characterized by smoking status and specific personality features. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 52 publications
8
76
2
2
Order By: Relevance
“…Comparison of the two groups for PPI in the placebo condition replicated the genotype differences in PPI (Roussos et al, 2008a) extending them to short, 30 ms intervals. These results confirm the importance of baseline PPI levels for the effect of dopaminergic drugs, which has been previously highlighted by different research groups (Swerdlow et al, 2003;Csomor et al, 2008) and strengthen our formulation of an interaction between PFC DA levels and PPI, according to an inverted U-shaped curve . These results also strengthen our previous suggestion that the PFC influences PPI levels, and by inference the early stages of attentional processing Bitsios et al, 2006;Roussos et al, 2008a).…”
Section: Discussionsupporting
confidence: 90%
“…Comparison of the two groups for PPI in the placebo condition replicated the genotype differences in PPI (Roussos et al, 2008a) extending them to short, 30 ms intervals. These results confirm the importance of baseline PPI levels for the effect of dopaminergic drugs, which has been previously highlighted by different research groups (Swerdlow et al, 2003;Csomor et al, 2008) and strengthen our formulation of an interaction between PFC DA levels and PPI, according to an inverted U-shaped curve . These results also strengthen our previous suggestion that the PFC influences PPI levels, and by inference the early stages of attentional processing Bitsios et al, 2006;Roussos et al, 2008a).…”
Section: Discussionsupporting
confidence: 90%
“…For example, we reported that the indirect dopamine agonist amphetamine reduced PPI only in normal adult males who exhibited baseline PPI levels in the upper 50% of a normal population (Swerdlow et al, 2003a), and a similar finding was reported by Bitsios et al (2005) using the dopamine agonists pergolide and amantadine. That the present finding detected essentially the opposite pattern (increased PPI among low gating individuals) using a dopamine antagonist supports the contention that dopamine function can truly modulate (ie decrease or increase) sensorimotor gating, depending on a 'set-point' level of gating function.…”
Section: Discussionsupporting
confidence: 78%
“…As previously reported in both rats (Swerdlow et al 2006b;Hadamitzky et al 2007) and humans (Swerdlow et al 2003b(Swerdlow et al ,2006bBitsios et al 2005), baseline levels of PPI strongly influence the impact of dopaminergic manipulations on PPI. Thus, we cannot convincingly report that the observed SD > LE sensitivity to AMPH after intra-NACc drug infusions reflects strain differences in AMPH sensitivity per se, vs. the physiological or arithmetic limitations imposed by a restricted range of PPI, vs. some interaction of these two processes.…”
Section: Discussionmentioning
confidence: 57%
“…Systemically administered DA agonists can both increase and decrease PPI, at different stimulus conditions and doses; such effects have been reported with both direct and indirect DA agonists (Swerdlow et al , 2003bMartin-Iverson & Else 2000). Thus, strain differences in sensitivity to the PPI-disruptive effects of DA agonists in SD vs.…”
Section: Introductionmentioning
confidence: 97%